2019
DOI: 10.1080/0886022x.2019.1655453
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing of Saudi Arabian patients with ADPKD

Abstract: Purpose: Autosomal dominant polycystic kidney disease (ADPKD) is characterized by progressive development of kidney cysts and enlargement and dysfunction of the kidneys. The Consortium of Radiologic Imaging Studies of the Polycystic Kidney Disease (CRISP) cohort revealed that 89.1% had either a PKD1 or PKD2 mutation. Of the CRISP patients with a genetic cause detected, mutations in PKD1 accounted for 85%, while mutations in the PKD2 accounted for the remaining 15%. Here, we report exome sequencing of 16 Saudi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 50 publications
2
8
0
Order By: Relevance
“…PKD1 is a large gene with 46 exons located on chromosome 16 (16p13.3) ( Consortium, 1994 ). There are six PKD1 pseudogenes ( PKDP1-P6 ) on chromosome 16 that have been six times and share high homology with PKD1 ( Bogdanova et al, 2001 ; Martin et al, 2004 ; Payne et al, 2021 ), and the GC content of some of these sequences is high ( Al-Muhanna et al, 2019 ). NGS sequencing alone has a poor capture efficiency for high-GC-content regions, resulting in some PKD1 gene mutations being undetected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PKD1 is a large gene with 46 exons located on chromosome 16 (16p13.3) ( Consortium, 1994 ). There are six PKD1 pseudogenes ( PKDP1-P6 ) on chromosome 16 that have been six times and share high homology with PKD1 ( Bogdanova et al, 2001 ; Martin et al, 2004 ; Payne et al, 2021 ), and the GC content of some of these sequences is high ( Al-Muhanna et al, 2019 ). NGS sequencing alone has a poor capture efficiency for high-GC-content regions, resulting in some PKD1 gene mutations being undetected.…”
Section: Discussionmentioning
confidence: 99%
“…This study is the first to combine MPCR amplification with targeted region sequencing (with an effective sequencing depth of 10,000×) to accurately detect suspected pathogenic sites. At present, there are many regions of PKD1 gene with high GC, but few areas that can’t be detected by next-generation sequencing ( Al-Muhanna et al, 2019 ). Therefore, mPCR could basically cover key areas, which is a good supplementary experiment.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, however, the diagnostic ability of WES for PKD1 is still uncertain. Al-Muhanna et al ( 44 ) reported that 100% coverage of PKD1 is possible with WES, whereas Ali et al ( 14 ) reported poor coverage of PKD1 at duplicated regions. The difference in reported sensitivity of WES may be due to different capture kits and data analysis methods.…”
Section: Discussionmentioning
confidence: 99%
“…Raw reads generated by the sequencer were first screened and low-quality reads were discarded. Detailed data analysis and candidate gene mutation filtering criteria have been previously described ( Al-Muhanna et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%